Interaksi Sosial Santri Pondok Pesantren Muhammadiyah Nurul Amin Alabio Tahun 1997-2020 - Fauziyah, Nurul; Susanto, Heri; Rochgiyanti, Rochgiyanti; Syaharuddin, Syaharuddin (Lambung Mangkurat University, 2022)
Nurul Amin Alabio Islamic Boarding School is a charity owned by Muhammadiyah which is located in Hulu Sungai Utara. The social life of students in Islamic boarding schools can be seen from how students can regulate their social relationships according to the teachings of their religion. This study aims to explain the social interactions of students that occur at the Nurul Amin Islamic Boarding School. This study uses a historical method that begins with heuristics, the author collects data, both primary and secondary data. The next step, author conducts criticism by testing the truth of the source through source triangulation. The third step is author interprets the sources obtained. The last step is historiography which is poured in the form of historical writings. The results showed that guidance in the social interaction of students in boarding school environment is carried out by the caretaker of the boarding school who is included in the organizational structure of the boarding school with the kyai as the leader. Social interaction is well established between fellow students, students with kyai, asatidz and the community. Based on the results of the study, it can be concluded that the social life of the students at Nurul Amin Islamic Boarding School is well developed, there is an integration between religious education and general science that is in accordance with the current era so that a strong student character is formed and can adapt to the times.